2015
DOI: 10.1242/dev.122663
|View full text |Cite
|
Sign up to set email alerts
|

The regulated elimination of transit-amplifying cells preserves tissue homeostasis during protein starvation in Drosophila testis

Abstract: How tissues adapt to varying nutrient conditions is of fundamental importance for robust tissue homeostasis throughout the life of an organism, but the underlying mechanisms are poorly understood. Here, we show that Drosophila testis responds to protein starvation by eliminating transit-amplifying spermatogonia (SG) while maintaining a reduced pool of actively proliferating germline stem cells (GSCs). During protein starvation, SG die in a manner that is mediated by the apoptosis of somatic cyst cells (CCs) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 50 publications
9
86
0
Order By: Relevance
“…We noticed that Spict-mRFP extensively overlapped with Lysotracker staining (Fig. 3A,B, see below for detailed Spict localization), which we previously showed to mark dying SGs17. These observations prompted us to ask whether spict plays a role in SG death.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…We noticed that Spict-mRFP extensively overlapped with Lysotracker staining (Fig. 3A,B, see below for detailed Spict localization), which we previously showed to mark dying SGs17. These observations prompted us to ask whether spict plays a role in SG death.…”
Section: Resultsmentioning
confidence: 66%
“…This argues that transit-amplifying cells, but not stem cells, may be a major point of regulation in response to changes in nutrient conditions. We have shown that starvation-induced SG death is triggered by apoptosis of CCs17. When CC death is blocked by inhibiting apoptosis, starvation-induced SG death was also blocked.…”
mentioning
confidence: 90%
See 3 more Smart Citations